Wireless sensor and robot networks : from topology control to communication aspects - Mitton, Nathalie; Simplot-Ryl, David (World Scientific Pub. Co., 2014)
Wireless sensor networks have gained much attention these last years thanks to the great set of applications that accelerated the technological advances. Such networks have been widely investigated and many books and articles have been published about the new challenges they pose and how to address them. One of these challenges is node mobility: sensors could be moved unexpectedly if deployed in an uncontrolled environment or hold by moving object/animals. Beyond all this, a new dimension arises when this mobility is controlled, i.e. if these sensors are embedded in robots. These robots cohabit with sensors and cooperate together to perform a given task collectively by presenting hardware constraints: they still rely on batteries; they communicate through short radio links and have limited capacities. In this book, we propose to review new challenges brought about by controlled mobility for different goals and how they are addressed in the literature in wireless sensor and robot networks, ranging from deployment to communications. -- Resumé vydavatele
Keywords: bezdrátové senzorové sítě; robotika; bezdrátové komunikační technologie; wireless sensor networks; robotics; wireless communication technology; kolektivní monografie; elektronické knihy; collective monographs; electronic books